The Value of Working Conditions in the United States and Implications for the Structure of Wages - Maestas, Nicole; Mullen, Kathleen J.; Powell, David; von Wachter, Till; Wenger, Jeffrey B. (American Economic Review, 2023)
We document variation in working conditions in the United States, present estimates of how workers value these conditions, and assess the impact of working conditions on estimates of wage inequality. We conduct a series of stated-preference experiments to estimate workers’ willingness to pay for a broad set of working conditions, which we validate with actual job choices. We find that working conditions vary substantially, play a significant role in job choice, and are central components of the compensation received by workers. We find that accounting for differences in preferences for working conditions often exacerbates wage differentials and intensifies measures of wage inequality. (JEL J22, J28, J31, J81)